Optimization of long rural feeders using a genetic algorithm - Wishart, M.; Ledwich, G.; Ivanovich, G.; Ghosh, Arindam (AIP, 2010)
This paper describes the optimization of conductor size and the voltage regulator location & magnitude of long rural distribution lines. The optimization minimizes the lifetime cost of the lines, including capital costs and losses while observing voltage drop and operational constraints using a Genetic Algorithm (GA). The GA optimization is applied to a real Single Wire Earth Return (SWER) network in regional Queensland and results are presented.